Lactic acid fermentation of banana peel using Lactobacillus plantarum : Effect of substrate concentration, inoculum concentration, and various nitrogen sources - Abdullah Abdullah; Yufrida Amalia (Reaktor, 2022)
Semeru Banana peel is an organic waste that is exclusively utilized as animal feed and does not harm the environment. The primary component of banana peels is carbohydrates, which can be used as a substrate during the fermentation process to produce lactic acid. The fermentation of banana peel flour with Lactobacillus plantarum strain FNCC 0020 was the main focus of this investigation. Variations in the concentrations of the substrate and inoculum as well as the impact of the type of nitrogen on lactic acid concentration were investigated. According to research findings, the big banana peel contains 70.52% carbs, 5.68% soluble protein, 3.115% fat, 6.74% water, 2.395% ash, and 13.38% crude fiber. While the inoculum variable was 0.5% v/v and the best substrate concentration variable was 17.5% w/v, the best lactic acid concentrations were 5.401 g/L and 8.586 g/L, respectively, as determined by HPLC (High-Performance Liquid) analysis. Banana peel flour only includes a modest amount of nitrogen (0.8295%), sulfate (0.037 grams), phosphate (1.6105%), and vitamin B1 (0.2315%), so additional nitrogen sources must be added. The production of lactic acid is shown to increase with the addition of various forms of nitrogen, with ammonium sulfate and ammonium phosphate (2:1) producing the greatest yields of 9.781 g/L and 14.255 g/L, respectively, of lactic acid, which is lower than lactic acid from yeast extract.